Ferroptosis: A New Promising Target for Lung Cancer Therapy - Rui Xiong; Ruyuan He; Bohao Liu; Wenyang Jiang; Bo Wang; Ning Li; Qing Geng (2021)
Ferroptosis is a new type of regulatory cell death that differs from autophagy, apoptosis, necrosis, and pyroptosis; it is caused primarily by the accumulation of iron and lipid peroxides in the cell. Studies have shown that many classical signaling pathways and biological processes are involved in the process of ferroptosis. In recent years, investigations have revealed that ferroptosis plays a crucial role in the progression of tumors, especially lung cancer. In particular, inducing ferroptosis in cells can inhibit the growth of tumor cells, thereby reversing tumorigenesis. In this review, we summarize the characteristics of ferroptosis from its underlying basis and role in lung cancer and provide possible applications for it in lung cancer therapies.